Endothelial cell loss after small incision cataract surgery - Thakur, SKD; Dan, A; Singh, M; Banerjee, A; Ghosh, A; Bhaduri, G (Nepalese Journal of Ophthalmology, 2011)
DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5273 Nepal J Ophthalmol 2011; 3(2): 177-180